2013
DOI: 10.1177/159101991301900315
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Core Needle Biopsy of Deep Suprahyoid Head and Neck Lesions in Untreated Patients

Abstract: This study aimed to evaluate the efficacy of CT-guided core needle biopsy (CNB) in the diagnosis of deep head and neck tumors in untreated patients. We retrospectively reviewed the records of ten consecutive CT-guided CNB procedures from ten patients without a related history from March 2004 to February 2012. The surgical results, treatment response and clinical follow-up were used as the diagnostic standards. All specimens were considered adequate. Nine out of ten cases matched the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…In the present study, we have reported the results of 74 CT-guided percutaneous core-needle biopsies performed in patients with suspicious masses in the deep spaces of the head and neck, a sample larger than those evaluated in previous studies (1,(10)(11)(12) . Sufficient material for histological analysis was obtained in all cases.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In the present study, we have reported the results of 74 CT-guided percutaneous core-needle biopsies performed in patients with suspicious masses in the deep spaces of the head and neck, a sample larger than those evaluated in previous studies (1,(10)(11)(12) . Sufficient material for histological analysis was obtained in all cases.…”
Section: Discussionmentioning
confidence: 96%
“…That is comparable to the 96.6% observed in our subgroup of 59 biopsies of masses in the suprahyoid space. In another study, Wu et al (11) found that core-needle biopsy resulted in a correct diagnosis in 9 of 10 patients with masses at the base of the skull and no known history of cancer. In a study of 15 biopsies of the deep spaces of the face and skull base in a mixed patient population (i.e., with and without a known history of cancer, as in the present study), Connor et al (10) reported a diagnostic accuracy of 87%.…”
Section: Infrahyoid Massesmentioning
confidence: 99%
See 3 more Smart Citations